Physical and physiological profiles of youth elite handball players during training sessions and friendly matches according to playing position - Oliveira, T.; Abade, E.; Gonçalves, B.; Gomes, I.; Sampaio, J. (International Journal of Performance Analysis in Sport, 2014)
This study aimed to describe youth elite handball players' performance during training sessions and friendly matches, according to specific playing positions. Seventeen male players from the Portuguese national team participated in this study (goalkeepers n=4, 1st line players n=6, 2nd line players n=7). The data was gathered during a one-week period (four training sessions) and two friendly matches using the following variables: training impulse (TRIMPMOD), countermovement jump, Abalakov jump and bodyload. The comparisons were made using percentages of variation from the match, considered as the baseline. The results showed that goalkeepers presented higher demands in training sessions. Comparatively to matches, the 1st line players presented higher Abalakov jump values after training sessions (˜8%). However, the high intensity zones of TRIMPMOD and bodyload per minute presented higher values during matches. The 2nd line players showed higher values of vertical jump after the training sessions. Additionally, the TRIMPMOD training presented values above 300% in low-intensity zones and ˜100% of variation in high-intensity zones from match. The amount of specific exercises performed by goalkeepers during the training sessions elicited a higher workload, and the lowest training stimuli for both 1st and 2nd line players suggested that training sessions do not replicate the match workload demands. Therefore, the identified match performance profiles among playing positions may help coaches to establish more specific and accurate training guidelines.